PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE DALAM MENINGKATKAN KOGNITIF BELAJAR EKONOMI SISWA PADA MATERI SISTEM PEMBAYARAN DI KELAS X SMA - Senty Siagian (Universitas Negeri Medan, 2020)
Abstract: Application of Think Talk Write Learning Model in Improving Student Economic Learning Cognitive on Payment System Material in Class X High School. The purpose of this study was to determine the cognitive learning outcomes of students while participating in learning on the subject matter of the Payment System through the application of the Think Talk Write learning model in class X. IIS-1 SMA Negeri 1 Lubuk Pakam T.A. 2017/2018. This research uses the action research model from Kemmis and Taggart, which is spiral from one cycle to the next. Each cycle includes planning, action, observation, and reflection, the subjects of this study were all students of class X IPS-1, namely 33 students. The results showed that the cognitive learning outcomes of students in Economics by applying Think Talk Write learning models in the first cycle reached an average of 69.1 with a classical completeness of 57.6% and the second cycle reached 81.8 with a classical completeness of 87.9% . Thus an increase in student cognitive learning outcomes and students' cognitive learning completeness is classically achieved in Economics subjects in class X IPS-1 of SMA Negeri 1 Lubuk Pakam in the Academic Year 2017/2018.Keywords: Learning Think Talk Write, Cognitive Learning.Abstrak: Penerapan Model Pembelajaran Think Talk Write dalam Meningkatkan Kognitif Belajar Ekonomi Siswa Pada Materi Sistem Pembayaran di Kelas X SMA. Tujuan penelitian ini adalah untuk mengetahui hasil belajar kognitif siswa selama mengikuti pembelajaran pada materi pokok Sistem Pembayaran melalui penerapan model pembelajaran Think Talk Write di kelas X. IIS-1 SMA Negeri 1 Lubuk Pakam T.A. 2017/2018. penelitian ini menggunakan model penelitian tindakan dari Kemmis dan Taggart, yaitu berbentuk spiral dari sklus yang satu ke siklus yang berikutnya. Setiap siklus meliputi planning, action, observation, dan reflection, Subjek penelitian ini adalah seluruh siswa kelas X IPS-1 yakni 33 orang siswa. Hasil penelitian menunjukkan bahwa hasil belajar kognitif siswa pada mata pelajaran Ekonomi dengan menerapkan model pembelajaran Think Talk Write pada siklus I mencapai rata-rata 69,1 dengan ketuntasan klasikal 57,6% dan siklus II mencapai 81,8 dengan ketuntasan klasikal 87,9%. Dengan demikian terjadi peningkatan hasil belajar kognitif siswa dan ketuntasan belajar kognitif siswa secara klasikal tercapai pada mata pelajaran Ekonomi di kelas X IPS-1 SMA Negeri 1 Lubuk Pakam Tahun Pelajaran 2017/2018.Kata Kunci: Pembelajaran Think Talk Write, Kognitif Belajar.